Elaboración de un manual de seguridad y salud de trabajo en la coordinación de mantenimiento de la ESPAM MFL - Calderón Sabando, Angela Yanet (2016)
This research was aimed at creating a Safety and Health Work Handbook for the Maintenance Coordination at the Escuela Superior Politécnica Agropecuaria de Manabí, to identify the risks in each of the processes taking place in that area, in order to avoid or mitigate accidents and occupational diseases in the staff. To meet the goals of the research, some visits to the department were carried out to collect information about work activities performed by workers, while an interview with analysts and maintenance assistants was conducted in order to understand the processes and procedures they perform. Field observation identified the risks they are exposed. The research was conducted within four phases: the first was the preparation of the record process in which they were described, with the goal of having the sequence of executed tasks. In the second phase, an analysis record of occupational hazards was prepared, where the type of risk is indicated, its causes and possible consequences, and further recommendations are presented in order to reduce them, in the third phase, the Safety and Health Work Handbook for the Maintenance Coordination was designed, according to the rules established by the Ministry of Labour Relations, finally, in the fourth stage the handbook was socialized with the respective staff for them to have knowledge of the contents.